Regional Shift to Bahasa Indonesia: Old Vernacular in a New Identity - Ninuk Kleden Probonegoro; Imelda - Imelda (Journal of Indonesian Social Sciences and Humanities, 2015)
The Gamkonora people are an ethnic group in Indonesia whose members have an outstanding linguistic ability: they are able to speak more than two languages, that is, two or more of Gamkonora, Ternatan-Malay, Ternate, andBahasa Indonesia. The use of these languages is related to the residual traces of the powers that have ruled the area in the history of North Maluku: the Ternate sultanate, European colonialists and Indonesian central government since independence. Re?ecting on the current language behaviour of the Gamkonoran younger generation, which tends to be the Indonesian language (read Malay); the authors question how far the Gamkonorans Indonesian language ability has in?uenced their Gamkonoran language and culture. Through ethnographic studies, the authors found that two languagesIndonesian and Gamkonoranhave di?erent roles in their culture. Therefore, the language shift toBahasa Indonesia by Gamkonoran youth will not replace the Gamkonoran language because the use of their tribal language is supported by their traditional institutions.